PENGEMBANGAN BAHAN AJAR MATEMATIKA BERBASIS PROJECT BASED LEARNING (PBL) SISWA SEKOLAH DASAR - Sustanto (PGSD UNIKA SANTU PAULUS RUTENG, 2022)
Development of Mathematics Teaching Materials Project Based Learning (PjBL) Elementary School Students. This research is development research. This study aims to develop mathematics teaching materials based on Project Based Learning (PjBL) for elementary school students with cube and cuboid building materials. This development product contains material on the concept of cube and cuboid space using the Sugiyono development model which includes: (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product trials, (7) product revisions, (8) usage trials, (9) final product refinement. The development model is used to develop mathematics teaching materials for students with slight modifications. Based on the results of the feasibility assessment of the validators consisting of material experts, linguists, and media experts, it can be seen that the development product is very feasible to use. In addition, the results of the attractiveness assessment in the form of responses from teachers and also responses from students through questionnaires can be obtained that the product development is also very interesting. From these results, it shows that the mathematics teaching materials developed based on Project Based Learning on the material of building cubes and cuboid for elementary school students are feasible to use. Keywords: Development of Teaching Materials, Matehematics, Project Based Learning